Membangun Generasi Digital: Pelatihan Pemrograman Web dan AI untuk Siswa SMA Negeri 2 Pematangsiantar - Victor Asido Elyakim P; Fransco Immanuel G Siahaan; Andrea Erich; Ahmad Ryandika; Ferdy Prayogi (Yayasan Literasi Sains Indonesia, 2025)
This activity is part of the Community Service Program aimed at introducing the basics of web programming to students of SMA Negeri 2 Pematangsiantar. The program was initiated due to the limited access and knowledge of students regarding web development technology, despite the high demand for such competencies in facing digital transformation across various sectors. The material was delivered interactively through lectures, live coding demonstrations, open discussions, and simple case studies. Topics covered include the basic structure of web development such as Frontend, Backend, and Databeses as well as three main technologies: HTML, CSS, and JavaScript. The activity was designed not only to help students understand the theoretical concepts but also to allow them to see practical implementations firsthand. Evaluation was conducted through observation of student participation and discussions, which indicated that the students were very enthusiastic, actively asked questions, and some were even interested in continuing to learn independently. These results demonstrate that this Program activity is effective in improving digital literacy and increasing student interest in web programming. It is hoped that similar activities can be conducted continuously to faster a generation ready to face future technological challenges